PERSONAL PROTECTIVE EQUIPMENT: THE PERSPECTIVE OF WORKERS WHO SUFFERED BURNS AT WORK - Caroline Lemos Martins; Michelle Barboza Jacondino; Liliana Antoniolli; Dione Lima Braz; Jéssica Stragliotto Bazzan; Maria Elena Echevarría Guanilo (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769211060 Aim: to get to know the importance of the use of personal protective equipment in the prevention of burn accidents at work according to employees. Method: a qualitative study, carried out at Referral Center for Burns Care, involving six workers who were victims of occupational burn accidents. The data collection took place between June and October 2012 through semi-structured interviews. The collected data were processed through content analysis. Results: the majority acknowledges the importance of using personal protective equipment that is appropriate to the occupational risks; nevertheless, the lack of or the inappropriate use may have favored the occurrence of occupational burns. Conclusions: employers and nursing professionals need to invest in professional training for the proper use of personal protective equipment with a view to achieving a safer work environment.